1992
DOI: 10.1073/pnas.89.4.1512
|View full text |Cite
|
Sign up to set email alerts
|

A human Id-like helix-loop-helix protein expressed during early development.

Abstract: The interaction of helix-oop-helix (HLH) proteins is known to regulate the differentiation of several different tissues, including mammalian muscle and the insect peripheral nervous system. In myoblasts, the products of myogenic HLH genes such as MyoD and ubiquitous HLH proteins such as E12 are present at constant levels throughout development. An E12 monomer and a MyoD monomer form a DNA binding heterodimer that activates muscle-specific genes. These two proteins are unable to dimerize in proliferating myobla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
77
0

Year Published

1995
1995
2016
2016

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 121 publications
(79 citation statements)
references
References 19 publications
(25 reference statements)
2
77
0
Order By: Relevance
“…The experimental inactivation of the Id2-gene locus does not lead to an apparent alteration of kidney development (Yokota et al, 1999). Nevertheless, our observation emphasizing a high level of Id2 transcription in the pronephros is in agreement with the strong accumulation of Id2 transcript reported in the developing kidney of Xenopus (Wilson and Mohun, 1995) and humans (Biggs et al, 1992) as well as in the adult kidney of trout (Rescan, 1997). Interestingly, an involvement of Id2 in regulating gene transcription in the kidney is suggested by in vitro data showing that Id2 interacts directly with Pax-2 and Pax-8 proteins, both of which are expressed in the kidney (Roberts et al, 2001).…”
Section: Distinct and Overlapping Expression Of The Idsupporting
confidence: 81%
“…The experimental inactivation of the Id2-gene locus does not lead to an apparent alteration of kidney development (Yokota et al, 1999). Nevertheless, our observation emphasizing a high level of Id2 transcription in the pronephros is in agreement with the strong accumulation of Id2 transcript reported in the developing kidney of Xenopus (Wilson and Mohun, 1995) and humans (Biggs et al, 1992) as well as in the adult kidney of trout (Rescan, 1997). Interestingly, an involvement of Id2 in regulating gene transcription in the kidney is suggested by in vitro data showing that Id2 interacts directly with Pax-2 and Pax-8 proteins, both of which are expressed in the kidney (Roberts et al, 2001).…”
Section: Distinct and Overlapping Expression Of The Idsupporting
confidence: 81%
“…As Id-1 expression promotes cellular proliferation and inhibits differentiation in many cell types, it is a natural focus of studies examining the molecular mechanisms of tumor development. Although not comprehensively studied, reports indicate that Id-1 is overexpressed in cells derived from several types of tumors, including pancreatic cancer, lung cancer, breast cancer, neuroblastoma, neuroepithelioma, astrocyte tumors, and endometrial cancers (Andres-Barquin et al, 1997;Biggs et al, 1992;Lin et al, 2000;Maruyama et al, 1999;Takai et al, 2001;Zhu et al, 1995). Indeed, recent studies have indicated that higher levels of Id-1 expression may be related to more aggressive tumors (Lin et al, 2000;Takai et al, 2001 …”
Section: Discussionmentioning
confidence: 99%
“…This gene represents one of four members of the mammalian "Idlike" dominant-negative HLH (dnHLH) gene family. The three other genes in this family are designated Id1 (Benezra, 19901, Id2 (Sun et al, 1991;Biggs et al, 1992), and Id4 (Riechmann et al, 1994), respectively. All four genes, although clearly distinct, share common features, such as the presence of a HLH dimerization domain and the lack of a basic DNA-binding domain.…”
Section: Discussionmentioning
confidence: 99%
“…One is designated Id2 (Sun et al, 1991;Biggs et al, 1992). Another gene has been characterized in the mouse as a gene called HLH462 (Christy et al, 1991) and in human as HEIR1 or HLHlR2l (Deed et al, 1993).…”
Section: Introductionmentioning
confidence: 99%